Do Fastskin swimsuits influence coordination in frontcrawl swimming? - Chollet, D.; Chavallard, F.; Lemaitre, F.; Seifert, L. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Fastskin suits (FS) have been greatly contested over the past several months, and the numerous studies on them have reported contradictory findings. The aim of this study was to compare the effects of FS on spatio-temporal parameters and the Index of Coordination (IdC) developed by Chollet et al. [1]. METHOD: In the first part of this study, 15 swimmers (6 females and 9 males) were asked to carry out a series of glide, buoyancy and passive torque tests and to swim a series of 25-m trials at four velocities (800, 400, 100 and 50 m), with and without FS. In the second clinical part of the study, a French international swimmer, specialized in short distances, carried out the same tests in SS condition and with three different FS. RESULTS: The results showed no significant differences in buoyancy, glide or passive torque with and without FS. A significant difference in IdC (p<.01): with FS: -9.562±5.87 versus without: -8.323±6.83 and propulsive phase (p<.01): with FS: 40.289±5.59 versus without: 41.609 ±6.81 was detected by looking at the average values of the four velocities. DISCUSSION: IdC was affected by wearing an FS, with a reduction in drag constraints for the same given speed, making each propulsive movement more effective. The compressive effect of these new FS, by reducing body volume and then damaging floatation, is offset by an improvement in the Cx. This compression is thus more useful for higher swim speeds. The case study of a real sprinter confirmed this change in coordination logic and further showed that, thanks to FS, he did not have to stack his actions to reach his highest speed. This study also suggested that the same FS could have different effects for other swimmers, each swimmer being unique: the same swimmer using a different swimsuit might be differently affected. The newest generation of FS, which did not improve buoyancy, did improve the glide and reduce drag. The swimmer thus had fewer constraints and was perhaps able to swim higher on the water, without needing to stack his actions. His coordination at a given speed when wearing an FS corresponded to coordination at a slower speed without an FS. REFERENCES: Chollet D., Chalies S., Chatard JC. (2000). A new index of coordination for the crawl: description and usefulness. Int J Sports Med, 21(1): 54-59.